Mites of the subgenus Microtimyobia (Acariformes: Myobiidae: Radfordia) and their host-parasite relationships with cricetid rodents (Cricetidae) - Bochkov, Andre V. (Zootaxa, 2011)
Myobiid mites of the subgenus Radfordia (Microtimyobia) (Acariformes: Myobiidae) associated with hosts of the subfamilies Arvicolinae and Cricetinae (Cricetidae) are revised. Three new species are described from voles: R. (M.) dinaromys sp. nov. from Dinaromys bogdanovi from Montenegro, R. (M.) golenishchevi sp. nov. from Eothenomys wardi from China (Mekong River), and R. (M.) pitymys sp. nov. from Microtus pinetorum from USA (Virginia). Radfordia (M.) lemnina micromys Fain and Lukoschus, 1976 syn. nov., R. (M.) lemnina mikado Uchikawa et al., 1997 syn. nov., R. (M.) stekolnikovi Bochkov and Mironov, 1998 syn. nov., and R. (M.) stenocrani Bochkov and Mironov, 1998 syn. nov. are synonymized with R. (M.) lemnina (Koch, 1941); R. (M.) rutila Fain and Lukoschus, 1977 syn. nov. and R. (M.) lemnina hata Uchikawa et al., 1997 syn. nov. are synonymized with R. clethrionomys Fain and Lukoschus, 1977; R. (M.) lemnina japonica Uchikawa et al., 1997 syn. nov. is synonymized with R. (M.) rufocani Bochkov, 1995; R. (M.) macdonaldi Gill and Strandtmann, 1977 syn. nov. is synonymized with R. (M.) arctica Fain and Lukoschus, 1977; R. (M.) cricetulus pakistanensis Fain and Hyland, 1980 syn. nov. is synonymized with R. (M.) cricetulus Fain, 1973. The female and male keys to all 21 currently recognized Microtimyobia spp. are provided. The host distribution of Microtimyobia spp. is analyzed. These mites serve as peculiar “markers” of particular host groupings and in many cases are useful tools to test some controversial hypotheses of cricetid phylogeny, including the intriguing problem of phylogenetic relationships of the Palearctic and Nearctic voles of the genus Microtus.